A multicenter study of blood component transfusion in patients with liver cirrhosis in China: Patient characteristics, transfusion practice, and outcomes. Issue 12 (December 2016) - Sun, Guixiang; Liu, Xiangfu; Liu, Zhiguo; Tan, Jianguo; Hao, Yiwen; Shan, Guiqiu; Luo, Qun; Wang, Deqing; Xing, Yanchao; Zhang, Xianqing; Gong, Jiwu; Kuang, Lihua; et al.
Abstract: Background: Cirrhosis is a complex acquired disorder of hemostasis and patients frequently receive blood transfusions. But there is very limited data on patterns of blood use at a patient level. Aims: To characterize blood use in cirrhotic patients in China and compare with recommendations to help identify areas where quality improvement strategies can be targeted. We also compared findings to a similar study undertaken in UK. Methods: A cross-sectional study was conducted in 11 hospitals over a 2-month period. Data were collected prospectively on each hospitalized cirrhotic patient to day 28. Results: 1595 cirrhotic patients were included and 20.6% were transfused. 48.2% of transfused patients received transfusion for bleeding, most commonly gastrointestinal bleeding (65.8%). The remaining 51.8% were transfused for non-bleeding indications. 32.5% of patients transfused for gastrointestinal bleeding with red blood cells had a pre-transfusion haemoglobin >7 g/dL. 89.1% of patients transfused frozen plasma for non-bleeding indications received them in the absence of a planned procedure. The patterns of blood transfusion in cirrhosis were different between China and UK. Of note, empirical prophylactic use of frozen plasma was more common in the Chinese study (89%) than in the UK (24%). Conclusion: Education and research should be implemented to improve patient blood management, especially in prophylactic frozen plasma use area.